2011
DOI: 10.4252/wjsc.v3.i11.104
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping of hematopoietic progenitor cells: Comparison between cord blood and adult mobilized blood grafts

Abstract: This study demonstrates that many different obstetric factors must be taken into account when processing and cryo-banking umbilical CB units for transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…Previous reports 14 suggested that maternal age is not significantly related to the umbilical cord blood and CD34 + cell count, as well as the number of NRBC’s in the umbilical cord blood. However, a previous report 28 showed that women >25 years old carry more TNCs, and younger maternal age was associated with a higher CD34 + cell concentration. 16 This observation may serve as a parameter during the selection and evaluation of the usefulness of a specific umbilical cord blood specimen.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Previous reports 14 suggested that maternal age is not significantly related to the umbilical cord blood and CD34 + cell count, as well as the number of NRBC’s in the umbilical cord blood. However, a previous report 28 showed that women >25 years old carry more TNCs, and younger maternal age was associated with a higher CD34 + cell concentration. 16 This observation may serve as a parameter during the selection and evaluation of the usefulness of a specific umbilical cord blood specimen.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, the antigen CD45 is one of the most important factors in the detection of CD34 + by different qualitative and quantitative protocols. 28 This is why it was included in our study panels.…”
Section: Discussionmentioning
confidence: 99%
“…In a prior study, Azouna et al found that the number of CD34 + cells was higher in the cord blood of neonates with higher birth weight (>3.5 kg) and born to older mothers [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…hPL has been explored as a substitute to FBS for cell culture and found to have advantages beyond that of simply eliminating xenogeneic concerns. Exposure of human mesenchymal stem cells (hMSCs) to hPL in vitro has positive effects, including increased proliferation, decreased doubling time, maintained immunophenotype and delayed senescence (Doucet et al , ; Muller et al , ; Reinisch et al , ; Schallmoser et al , ; Carrancio et al , ; Avanzini et al , ; Azouna et al , ; Flemming et al , ; Griffiths et al , ; Rubio‐Azpeitia and Andia, ).…”
Section: Introductionmentioning
confidence: 99%